Texts & contexts of the oldest Runic inscriptions - Looijenga, Tineke (Northern world, 2003)
This work gathers all older fufark inscriptions found in Denmark, Germany, England, France, the Netherlands, Belgium, Switzerland, Hungary, Bosnia, Rumania, Norway and Sweden. It includes essays on early runic writing, the contexts of runic objects, and a theory on the origin of runic writing.